Assess the Knowledge Regarding Food and Vegetable Sanitation among Housewives in Selected Areas of Pune City - Stephina Fernandes1 , Sharadha Ramesh2 , Jennifer. Anthony1 , Poonam Yadav1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In order to preserve our health and remain healthy, it is of upmost importance to maintain the quality offood we intake and avoid contamination. To achieve this, proper sanitation of the food and vegetables weingest is required. The poor knowledge of food sanitation causes several food-borne disease and varioushealth issues and in turn puts extra strain on our Health Sector. Hence, it is important to prevent the foodfrom getting contaminated with microbes or toxic chemicals, and follow healthy food sanitation practices.To achieve this, food safety at the household level and knowledge regarding handling food is essential.The aim of this study was to gain and scrutinize the knowledge related to food and vegetable sanitationamong housewives who cook the food at home. Objective: 1) To assess knowledge regarding foodsanitation among housewives in selected areas of Pune city. 2) To assess knowledge regarding vegetablesanitation among housewives in the selected areas of Pune city. Result: The analysis shows that 7.94%of housewives have excellent knowledge regarding cleaning of vegetables and fruits, 23% of housewiveshave very good knowledge, 23% of housewives have good knowledge while 44.4% of housewives haveaverage knowledge. Also 15.87% of housewives have excellent knowledge regarding separation (keepapart) of food & vegetables, 7.6% of housewives have very good knowledge, 28.57% housewives have goodknowledge while, 47.6% of housewives have average knowledge. Also 7.94% of housewives have excellentknowledge regarding cooking at safe temperatures, 15.87% of housewives have very good knowledge,25.39% housewives have good knowledge while, 50% of housewives have average knowledge. And 6.35%of housewives have excellent knowledge regarding chilling i.e refrigerating the food items and vegetables,15.87% of housewives have very good knowledge, 31.7% housewives have good knowledge while, 46.0% ofhousewives have average knowledge. Conclusion: The housewives have satisfactory knowledge regardingseparation and cleaning of food and vegetables, also they have less knowledge regarding cooking at safetemperature and the refrigerating of the food and vegetables. Hence, they need to be motivated to followgood food and vegetable practices in order to prevent contamination of food as well as to reduce the rate offood-borne illnesses.